Perceived Vulnerability and Climate Change Impacts on Small-Scale Fisheries in Davao Gulf, Philippines - Macusi, Edison D.; Camaso, Kezia L.; Barboza, Anna; Macusi, Erna S. (Frontiers in Marine Science, 2021)
The small-scale fisheries play a critical role for the food security and income of coastal fishing communities. However, climate change impacts and variability are affecting fishers, their communities, and fishing grounds. This study aims to determine the perceived impacts of climate change and vulnerability of small-scale fisheries in selected fishing communities around the Davao Gulf. A semi-structured questionnaire was used to gather data on the perception of respondents (N=220) on the impacts of climate change on their livelihood and communities and data was validated using seven focus groups (N=15). Five study sites were chosen for the study (Governor Generoso, Lupon, Davao City, Malita and Don Marcelino). Principal component analysis (PCA) was used to reduce the sources of vulnerabilities and number of impacts of climate change and regression was used to determine factors influencing the catch per unit effort (cpue). The PCA results showed that for the sources of vulnerability, coral bleaching, inadequate food, lack of credit access, changes in weather pattern and hotter temperature contributed highly. For the climate change impacts, the factors, less seasonality, unclear reproductive patterns, diseases in the catch, invasive species, decrease in catch and venturing farther to fish offshore also contributed highly. Further analysis showed that disease and invasive species, decrease in fish catch and fishing farther offshore and monthly income influenced the cpue of the fisheries. Suggested interventions include better credit access, apprehension of illegal fishers, upgrading of skills, supplemental livelihood, and information dissemination on climate change adaptation strategies.